Structural characterization and in vitro hypoglycemic activity of a glucan from Euryale ferox Salisb. seeds. (1st April 2019) - Zhang, Wen-Na; Su, Ri-Na; Gong, Li-Li; Yang, Wei-Wei; Chen, Juan; Yang, Rui; Wang, Ya; Pan, Wen-Juan; Lu, Yong-Ming; Chen, Yan
Graphical abstract: Highlights: A new glucan EFSP-1 was firstly obtained from the seeds of Euryale ferox Salisb. Structure of EFSP-1 was characterized by FT-IR, GC–MS and NMR. EFSP-1 possessed high hypoglycemic activities in vitro . EFSP-1 could improve insulin resistant through PI3K/Akt signal pathway in IR HepG2 cells. Abstract: In this research, a polysaccharide fraction (EFSP-1) was obtained from the seeds of Euryale ferox Salisb. by DEAE sepharose FF and Superdex ™ 75 gel chromatography. The average molecular weight (Mw) of EFSP-1 was 8.75 kDa. Monosaccharides composition analysis indicated that EFSP-1 was a glucan. The structure of EFSP-1 was characterized by analysis of FT-IR, GC–MS and NMR, which indicated that the backbone of EFSP-1 was mainly composed of (1→4)- α -D-Glc p with branches substituted at O-6 and terminated with T- α -D-Glc p . Moreover, the hypoglycemic effect of EFSP-1 was investigated by establishing insulin resistance HepG2 and 3T3-L1 cells. The results showed that EFSP-1 could increase glucose consumption by up-regulating the expression of GLUT-4 via activating PI3K/Akt signal pathway in IR cells. Hence, EFSP-1 could be a potential functional food to ameliorate insulin resistance for diabetes therapy.